(3GdCMcGe GdSdWGfjIs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s ((3GHh SYjO fUQ Hf eMeO Hf Sdje GdQGHW GdaQGA s)
(3ChdgG (B:s
(3GdMeO ddg GdPi GhVM dfG eYGde GdOjf hdeG cGfJ GdGMcGe GdSdWGfjI HhdGI GdGehQ GNU hcGf GeJRGLgG HLejY GdGMcGe jbWYge GaQOJ dg cJGHkG GeJKdJ ajg GeQ ef dReJ WGYJg s
(3BNQgG (B:s
(3hEf cGf GcKQ cJGHfG gPG jTJed Ydi eG bO CZadJ GdabgGA Ch bUQhG ajg aPcQfG eG CZadhg hGSJhajfG eG bUQhG ajg hGf GSCd Gddg JhajbkG deG JhNjJg hYRekG Ydi eG fhjJg Yfg heTjJg hgh MSHi hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B19s
Keywords: (3GdSjGSI hGdGLJeGYs